Australian, Irish, and Swedish women's comfort levels when breastfeeding in public - Louise Gallagher; Vivienne Brady; Lesley Kuliukas; Charlotta Dykes; Christine Rubertsson; Yvonne L. Hauck (BMC, 2023)
Abstract Background Despite a flux of global initiatives to increase and sustain breastfeeding rates, challenges persist. The decision to commence and sustain breastfeeding is influenced by multiple, complex factors. Feelings of social embarrassment, shame, fear of judgement, and lack of confidence when breastfeeding in public, compound women's decisions to breastfeed and may result in formula feeding or early cessation of breastfeeding. A greater understanding of where and how women feel most comfortable when breastfeeding in public can assist in designing interventions to support the initiation and continuation of breastfeeding. Methods A cross-sectional survey was conducted with women living in Australia (n = 10,910), Sweden (n = 1,520), and Ireland (n = 1,835), who were currently breastfeeding or who had breastfed within the previous two years. Our aim was to explore where, and how often women breastfeed in public and to compare their levels of comfort when breastfeeding in public. Data were collected in 2018 using an anonymous online survey over a four-week period in Ireland, Australia, and Sweden, and were analyzed using SPSS Version 25. Results Most respondents were highly educated, with over 70% in each country reporting having a university or college degree. Observing women breastfeeding in public was more commonly reported to be a weekly or daily occurrence in Sweden (24.5%) and Australia (28%), than in Ireland (13.3%). Women in the participating countries reported breastfeeding in public most commonly whenever their babies needed feeding. Very few women never or rarely breastfed publicly. Coffee shops/cafes, restaurants, and parks were the most popular locations. In all three countries, partners were reported to be very supportive of breastfeeding in public, which enhanced breastfeeding women's comfort levels. When asked to score out of a maximum comfort level of 10, women reported higher mean levels of comfort when breastfeeding in front of strangers (Ireland M = 7.33, Australia M = 6.58, Sweden M = 6.75) than with those known to them, particularly in front of their father-in-law (Ireland M = 5.44, Australia M = 5.76, Sweden M = 6.66 out of 10), who scored lowest in terms of women's comfort levels. Conclusion This study offers important insights into the experiences and comfort levels of women breastfeeding in public. Limitations include the anonymous nature of the surveys, thus preventing follow-up, and variances in terminology used to describe locations across the three settings. Recommendations are made for research to determine the relationships between the frequency of breastfeeding in public and breastfeeding women's perceived comfort levels, the influence of family members' perceptions of breastfeeding in public and women's experiences, and the experience of women who feel uncomfortable while breastfeeding in public, with a view to developing support measures.